Pathways to reflective learning and teacher development: insights from teacher trainees’ diaries - Gurnam Kaur Sidhu,; Sarjit Kaur, (penerbit ukm, 2010)
Teacher trainees going out to schools for their teaching practicum are often required to keep reflective diaries to help provide them with valuable insights into their own thoughts, beliefs and practices. Reflective writing is a form of authentic communication, more superior to talk as it helps shape our thinking. This process of shaping experiences are more explicit because writing requires great deliberation and word choice leading to more explicitness in expression. Call it ‘a humbling process’ or a ‘mirror of the mind’; learning diaries enable learners to take the private and individual learning journey towards self-development and self-realization. This study investigated the professional development of two teacher trainees who underwent a three-month long teaching practicum in Malaysian public schools. Data collected from the diaries were triangulated with open-ended interviews. The findings revealed that both students felt that their teaching practicum was a meaningful learning experience. Further probing indicated that through over critical reflection, one progressed from awareness of theoretical concepts to involvement and implementation, while the other was able to move onto higher levels of creation and transcendence where she could one day become a teacher to others. More importantly this reflective journey helped teacher trainees chart their beliefs and perceptions on the teaching and learning process and what future pathways they wanted to take.